(untitled) (American Journal of Islam and Society, 2020)
Since its inception in 1947, the significance of Pakistan in the theater of global politics and world history cannot be overstated. Pakistan the idea inspired the debates of the brightest intellectuals of the early twentieth century in colonial India, as they charted a way out from brutal British imperial domination. Pakistan the dream continues to inform the hearts of a third generation of citizens since birth—and those of millions of others who form the extensive Pakistani diaspora which colors nearly every other country in the world. To read the full book review, download the PDF file on the right.